Temperature adaptations of enzymes of a mucous membrane of intestines of Russian and Siberian sturgeons and their hybrid - D. A. Bednyakov (Юг России: экология, развитие)
In work temperature adaptations of enzymes of a mucous membrane of intestines of Russian, Siberian sturgeons and their hybrid ROLO are investigated. It is confirmed that temperature adaptations of digestive system poikilothermic organisms are realised mainly thanks to reorganisations of fermental systems. The assumption that evolutionary adaptation of hydrolytic function of intestines of fishes to temperature conditions of an inhabitancy takes place, apparently, is made.